On the use of multiple criteria distance indexes to find robust cash management policies. Issue 3 (3rd July 2019) - Salas-Molina, Francisco; Rodriguez-Aguilar, Juan A.; Pla-Santamaria, David
ABSTRACT: Cash management decision-making can be handled from a multiobjective perspective by optimizing not only cost but also risk. Nevertheless, choosing the best policies under a changing context is by no means straightforward. To this end, we rely on compromise programming to incorporate robustness as an additional goal to cost and risk within a multiobjective framework. As a result, we propose to calculate robustness as a multiple criteria distance index that is able to identify the best compromise policies in terms of cost and risk. Such policies are also robust to cash flow regime changes. We show its utility by transforming the Miller and Orr's cash management model into its robust counterpart using real data from an industrial company.